IMPLEMENTING A CROP-LIVESTOCK INTEGRATION SYSTEM AND EVALUATION OF CORN SILAGE YIELD AS A FUNCTION OF SOIL MANAGEMENT - COLET, MARCELO JOSÉ; GARBUIO, PAULO WILLIAM; DELALIBERA, HEVANDRO COLONHESE; SVERZUT, CLÁUDIO BIANOR; ANDRADE, JOÃO BATISTA DE (Revista Brasileira de Engenharia de Biossistemas, 2008)
The crop-livestock system is being used more often by Brazilian farmers, as a way to diversify the income sources as well to recover degraded soil under pasture. Also, these systems contribute to the recovery of de productive capability of the pastures, and corn silage can be used as a supplemental feed. This feed when used as supplement can also contribute for the increase the livestock systems productivity. This research aimed to evaluate the corn yield to produce silage according to the soil management used in the implantation of a crop-livestock system. An experiment was evaluated at the Instituto de Zootecnia de Nova Odessa, with the lime addition, soil chisel plow and gypsum application as the treatments, in four plots of Brachiaria brizantha cv. Marandú pasture. After the experimental setup, the corn was cropped and the green mass and dry mass yield of silage was evaluated. The chisel plow led to significant increase in the yield of green mass and dry mass of silage. The superficial lime application and the lime application divided in surface and subsurface, as well as the gypsum application, did not influence the corn green mass and dry mass yield